Ta‘limda fanlararo integratsiyani ta‘minlashda innovatsion ta‘lim texnologiyalardan foydalanish - Zaripova, D.A (ILIM hám JÁMIYET, 2023)
This article presents the effectiveness of the teaching methodology using innovative educational technologies in providing interdisciplinary integration of education.